Using equine assisted learning to boost character skills and academic achievement among university students - Siti Salasiah Mokri; Norhana Arsad; Norazreen Abd Aziz; Norbahiah Misran (Penerbit Universiti Kebangsaan Malaysia, 2023)
Recreational horseback riding has been recognized for its therapeutic benefits, particularly through direct human-horse interactions. Despite known positive impacts of horse’s interactions with humans, there is no reported study discussing the relationship of equine assisted therapy and character skill development among university students. This paper examines the impact of equine assisted learning (EAL) on university students who struggled academically in the previous semester. Twelve students participated voluntarily in the program, engaging the study participants in experiential learning of EAL sessions at Majlis Ekuin Malaysia horse stable. The learning sessions, each conducted for nearly three hours, involved tasks to complete including stable cleaning, grooming, feeding, and leading horses. Study participants were requested to complete questionnaires before and after the EAL program to assess their character skill development, measured through "Habits of Minds." Students’ academic results in terms of grade point average (GPA) achieved in the previous semester before EAL were compared with their GPA for the current semester after the students had been involved in the EAL program. Results of the study revealed collective improvements in the “Habits of Minds'' attributes of Persistence, Flexible Thinking, Responsible Risk-Taking, and Empathetic Listening after the EAL program. However, the attribute Managing Impulsivity was slightly impaired. Interestingly, all students’ GPA after the EAL program had also improved compared to their previous GPA. The (mean + standard deviation) of the students’ GPA after EAL intervention (2.21 + 0.59) is significantly increased compared to that before the EAL intervention (1.66 + 0.67) with p = 0.045. The overall finding from this study suggests that the practical benefits of the EAL program can enhance character skills development that can lead to better academic results among university students.